COMPARISON OF ENTERIC-COATED ASPIRIN TABLETS BY DIFFERENT PRODUCERS: DISSOLUTION TEST RESULTS - V. V. Rafalsky; S. O. Losenkova; A. V. Krikova; K. I. Maksimenkova; A. N. Baglikov (Российский кардиологический журнал, 2010)
.